2014
DOI: 10.5012/bkcs.2014.35.8.2317
|View full text |Cite
|
Sign up to set email alerts
|

In silico Study on the Interaction between P-glycoprotein and Its Inhibitors at the Drug Binding Pocket

Abstract: P-glycoprotein (P-gp) is a member of the ATP-Binding Cassette transporter superfamily and mediates transmembrane efflux of many drugs. Since it is involved in multi-drug resistance activity in various cancer cells, the development of P-gp inhibitor is one of the major concerns in anticancer therapy. Human P-gp protein has at least two "functional" drug binding sites that are called "H" site and "R" site, hence it has multi-bindingspecificities. Though the amino acid residues that constitute in drug binding poc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…There were some binding residues that contacted with rhodamine B presenting in Hoechst 33342 binding pocket. A similar observation was also reported by Kim et al 27 , where they observed the top-ranked docking Hoechst 33342 poses interacted with the assigned R-site. Fluorescence resonance energy transfer (FRET) studies pointed out that the Hoechst 33342 binding site is likely located 10−14 Å below the membrane surface, within the cytoplasmic leaflet of the membrane 28 .…”
Section: Docking Characterization Of Substrates Binding Sites In Human P-gpsupporting
confidence: 88%
“…There were some binding residues that contacted with rhodamine B presenting in Hoechst 33342 binding pocket. A similar observation was also reported by Kim et al 27 , where they observed the top-ranked docking Hoechst 33342 poses interacted with the assigned R-site. Fluorescence resonance energy transfer (FRET) studies pointed out that the Hoechst 33342 binding site is likely located 10−14 Å below the membrane surface, within the cytoplasmic leaflet of the membrane 28 .…”
Section: Docking Characterization Of Substrates Binding Sites In Human P-gpsupporting
confidence: 88%
“…To have greater confidence in the results obtained by our molecular docking method, we evaluate it with three known P-glycoprotein-binding compounds: verapamil, Rhodamine123, and Hoechst 33342. As a crystal structure of one of the most-studied ligand binders of P-glycoprotein is unavailable, we based our results in the interaction residues of each ligand with the two models of hP-gp; many works have been done in this manner [36,37,41]. In Figure 13, the best poses of each ligand in this study over the mP-gp model are displayed.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we used two approximations for the homology modeling, one considering the sequence homology, and the other considering the structural features of the TM helices. For the first case, we employed the crystal structure of mus musculus P-glycoprotein (mP-gp) as a template (PDB:3G61) for the construction of the homology model, because of the high sequence homology (83%) between this protein and human P-glycoprotein (hP-gp), an approximation used by Namseok Kim et al [36]. On the other hand, Safiulla Basha et al used the crystal structure of Caenorhabditis elegans P-glycoprotein (cP-gp) as a template (PDB:4F4C) for the construction of the homology model, which has a sequence homology of 46% compared to hP-gp, because of the more reliable orientation of the TM3, TM4, and TM5 helices [37].…”
Section: Methodsmentioning
confidence: 99%
“…Homology model-based study provides theoretical suggestions on probable binding poses and sites (Klepsch et al 2011). Recently, with the binding pocket structure obtained from the homology modeled P-gP structure, four probable binding sites were proposed (Kim et al 2014b).…”
Section: Transportermentioning
confidence: 99%